2016
DOI: 10.5301/jva.5000616
|View full text |Cite
|
Sign up to set email alerts
|

Performance of physical examination versus ultrasonography to detect stenosis in haemodialysis arteriovenous fistula

Abstract: PE has shown a moderate accuracy to detect stenosis. With non-ultrasonography availability Haemodialysis Units can get benefit to optimize VA survival and professionals should improve its basic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
2
9
0
3
Order By: Relevance
“…Six prospective observational studies (Table 3) have compared the detection of stenosis by PE of the AVF to the gold standard tests, Doppler ultrasound (two studies) and angiogram (four studies). 2,3,[22][23][24][25] The PE was done by interventional nephrologists, nephrology fellows, nephrologists, and interventional radiologists. In one study, we do not know who did the PE.…”
Section: Confirming the Findings Of Pe With Angiography And Ultrasounmentioning
confidence: 99%
“…Six prospective observational studies (Table 3) have compared the detection of stenosis by PE of the AVF to the gold standard tests, Doppler ultrasound (two studies) and angiogram (four studies). 2,3,[22][23][24][25] The PE was done by interventional nephrologists, nephrology fellows, nephrologists, and interventional radiologists. In one study, we do not know who did the PE.…”
Section: Confirming the Findings Of Pe With Angiography And Ultrasounmentioning
confidence: 99%
“…(24,30,54) Entretanto, anos de experiência profissional em geral não devem ser critérios presuntivos da qualidade do monitoramento, cabendo sempre execução de treinamentos focados nos elementos de relevância de avaliação, de forma a garantir um melhor resultado no monitoramento. (9,17) Apesar do predomínio de avaliações por profissionais de enfermagem, os estudos não reportaram uma perspectiva abrangente orientada pelo processo de enfermagem, teoria ou sistema de classificação de enfermagem. Entende-se que tal perspectiva possa fornecer suporte para o cuidado prestado e contribuir para o fortalecimento científico da enfermagem, devendo contemplar todos os estágios do processo, com intuito de promover a qualidade de vida do paciente renal crônico submetido à hemodiálise.…”
Section: Discussionunclassified
“…(10,(13)(14)(15) No geral, ambas avaliações são complementares. (16)(17)(18) A avaliação física do monitoramento de disfunção do acesso na fase de maturação, foco deste artigo, tem sido considerada conveniente, simples, econômica e de relevância. (16) Estudo desenvolvido em uma unidade radiológica demonstrou que esta avaliação obteve altos valores de sensibilidade (82%) para detecção de estenose, sendo o exame físico uma ferramenta útil, especialmente quando aplicado em centros que não dispõem da ultrassonografia para vigilância.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…However, the accuracy of clinical diagnosis of a stenosis depends on the stenosis location, on vascular access and patient's characteristics (depth, flow volume, vein branching, and compliance), and highly on the experience of the hemodialysis unit team, which is not always optimal. 3,4 In a recent study by Castro et al, 5 the clinical suspicion on AVF stenosis was not confirmed in 27% of cases. Some stenoses remain clinically asymptomatic, which explains at least part of the "sudden" thrombosis that develops without any warning signs.…”
Section: Introductionmentioning
confidence: 92%